Micromorphological characteristics of the species of Pholiota (Strophariaceae, Basidiomycota) in pure culture - Regeda, L.V.; Bisko, N.A. (Український ботанічний журнал, 2019)
The article presents results of the research on micromorphology of vegetative mycelia of eight species of the genus Pholiota from the IBK Mushroom Culture Collection of the M.G. Kholodny Institute of Botany, National Academy of Sciences of Ukraine. Using scanning electron microscopy and light microscopy, the micromorphological structures specific to these species were studied in order to enable their identification in pure culture. New data on micromorphology of Pholiota species are given. A set of micromorphological structures was observed for this genus, namely clamp connections, chlamydospores, arthrospores, anastomoses, crystals on hyphae, hyphal rings, rhizomorphs, pellicle spots, hyphae ornamentation, and secretory hyphae. For the first time a detailed study of microstructures of P. alnicola, P. limonella, P. nameko, P. populnea, and P. subochracea was conducted. Secretory hyphae and vacuolized mycelia in pure culture were noticed only for P. populnea. For P. subochracea, various hyphae ornamentation on vegetative mycelium was demonstrated. New information about the presence of hyphal rings for three Pholiota species, P. alnicola, P. limonella, and P. subochracea, is presented. Представлені результати досліджень мікроморфології вегетативного міцелію восьми видів роду Pholiota з Колекції культур шапинкових грибів Інституту ботаніки ім. М.Г. Холодного НАН України (ІВК). За допомогою світлової мікроскопії та сканувальної електронної мікроскопії були вивчені мікроморфологічні структури, специфічні для цих видів та необхідні для їхньої ідентифікації в чистій культурі. Наведено нові дані з мікроморфології видів роду Pholiota. Відмічено сукупність мікроморфологічних структур, а саме: пряжки, хламідоспори, артроспори, анастомози, кристали на гіфах, гіфальні кільця, ризоморфи, міцеліальні плівки, секреторні гіфи на вегетативному міцелії, орнаментація гіф. В нашому дослідженні вперше проведено детальне вивчення мікроструктур P. alnicola, P. limonella, P. nameko, P. populnea та P. subochracea для уточнення морфологічних характеристик та надійної ідентифікації цих видів у чистій культурі. Лише для P. populnea було відмічено існування секреторних гіф і вакуолізованого міцелію. Для P. subochracea отримана інформація щодо орнаментації гіф на вегетативному міцелії. Гіфальні кільця вперше виявлені у трьох видів – P. alnicola, P. limonella і P. subochracea.